Two Interviews with Ericka Huggins - Platt, Anthony M. (Social justice, 2013)
An interview with activist Ericka Huggins is presented. Topics discussed include the first time when she questioned why people lived in their cars in the snow while wealthy people in the Northwest and on Capital Hill had warm houses, who her participation in the March on Washington at age 15 transformed her life and her arrest for conspiracy with the intent to commit murder and her imprisonment when her daughter was 3-1/2 months old.